2008
DOI: 10.2320/matertrans.mep2007257
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Guinier-Preston Zones in an Mg-2 at%Gd-1 at%Zn Alloy Studied by Transmission Electron Microscopy

Abstract: Planar Guinier-Preston zones (GP-zones) parallel to a basal plane of an Mg hexagonal lattice are found together with 0 and 1 precipitates, which have been found in Mg-Gd alloys, in an Mg-2 at%Gd-1 at%Zn (Mg 97 Gd 2 Zn 1 ) alloy aged at 200 C for 150 hrs. From the combination of high-resolution transmission electron microscopy (HRTEM) and high-angle annular detector dark field scanning transmission electron microscopy (HAADF-STEM), we can determine the structure of the GP-zone, in which Gd and/or Zn atoms occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 16 publications
7
36
0
Order By: Relevance
“…It is hence likely that the conditions applied by Nishijima and Hiraga 7) could lead to an advanced stage of the precipitation sequence. In another alloy system,a Mg0.99 at% Sm alloy aged at 473 K, 13) some isolated hexagonal contrasts and short zigzag lines similar to those reported in the present work were reported. In reference 13 the authors concluded that the hexagonal arrangement of Sm atoms is stably formed as nuclei in the early stage of the formation of precipitates.…”
Section: )supporting
confidence: 89%
“…It is hence likely that the conditions applied by Nishijima and Hiraga 7) could lead to an advanced stage of the precipitation sequence. In another alloy system,a Mg0.99 at% Sm alloy aged at 473 K, 13) some isolated hexagonal contrasts and short zigzag lines similar to those reported in the present work were reported. In reference 13 the authors concluded that the hexagonal arrangement of Sm atoms is stably formed as nuclei in the early stage of the formation of precipitates.…”
Section: )supporting
confidence: 89%
“…3,4) Since the last several years, it has been widely demonstrated that the formation of GP-zones as well as their microstructural modification also occur in various precipitation hardened Mg-based alloys having the hexagonal close packed (HCP) matrix. [5][6][7][8][9] Recently, Nishijima et al reported on the GP-zones precipitated in an Mg-Gd-Zn alloy. 9) According to their results, the GP-zones are formed in an Mg 97 Gd 2 Zn 1 alloy, when it is annealed at 200 C for 150 h after quenching from 520 C in water, co-existing with other precipitates ( 0 and 1 phases).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Recently, Nishijima et al reported on the GP-zones precipitated in an Mg-Gd-Zn alloy. 9) According to their results, the GP-zones are formed in an Mg 97 Gd 2 Zn 1 alloy, when it is annealed at 200 C for 150 h after quenching from 520 C in water, co-existing with other precipitates ( 0 and 1 phases). In addition, the GP-zone is composed of two (Gd, Zn)-rich layers separated by an Mg layer parallel to close-packed planes of the HCP Mg-matrix, and (Gd, Zn) atoms are located at ordered positions in the (Gd, Zn)-rich layers with an atomic ratio of Mg 2 (Gd, Zn).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] However, electron diffraction and HRTEM used in previous studies are not sufficient tools to obtain detailed information about crystals structures and microstructures of fine precipitates. Recently, some of the authors have studied precipitates in Mg-Gd, 6,7) Mg-Y, 8) Mg-Cu-Y 9) and Mg-Zn-Gd 10) alloys by the combination of HRTEM and HAADF-STEM, and successfully obtained valuable information about crystal structures and microstructures of fine precipitates, which cannot be established by only HRTEM. In particular, atomic-scaled HAAED-STEM observations make possible to image directly arrangements of RE atoms in the Mg-matrix lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Mg-Sm alloy system is a good sample for the comparison with precipitate phases in other Mg-RE alloys examined in the previous papers. [6][7][8][9][10] In the present paper, the morphologies and crystal structures of precipitates in the Mg-Sm alloy system will be revealed from HRTEM and HAADF-STEM observations.…”
Section: Introductionmentioning
confidence: 99%